2011
DOI: 10.1007/s00381-011-1448-3
|View full text |Cite
|
Sign up to set email alerts
|

Keystone design perforator island flap for closure of myelomeningocele

Abstract: Whilst primary closure remains an option for myelomeningocele closure, primary repair of larger defects can lead to closure site tension, stretching of inelastic scar tissue and inadequate soft tissue cover. In this small series, we have demonstrated the use of keystone design perforator island flap closure as an alternative for larger and more complex lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 9 publications
2
39
1
Order By: Relevance
“…When designed over mobile muscle bellies (e.g., in the proximal thigh), release of the deep fascia even on one side can provide significant advancement subject to local tissue quality. 23 The keystone flap has demonstrated a growing diversity of clinical applications, 7-9 including coverage of large defects of the trunk, 10 limb, 13,14,21,26 groin, 23 perineum, 15 myelomeningocele, 27 and head and neck. 28 Previous modifications include a "yin yang" reconstruction, 29 including partial undermining and interdigitation of bilateral keystone flaps, 7 and the "omega variant," where both limbs of a single keystone are folded into a horseshoe shape.…”
Section: Key Points Of Flap Harvest Potential Advantagesmentioning
confidence: 99%
“…When designed over mobile muscle bellies (e.g., in the proximal thigh), release of the deep fascia even on one side can provide significant advancement subject to local tissue quality. 23 The keystone flap has demonstrated a growing diversity of clinical applications, 7-9 including coverage of large defects of the trunk, 10 limb, 13,14,21,26 groin, 23 perineum, 15 myelomeningocele, 27 and head and neck. 28 Previous modifications include a "yin yang" reconstruction, 29 including partial undermining and interdigitation of bilateral keystone flaps, 7 and the "omega variant," where both limbs of a single keystone are folded into a horseshoe shape.…”
Section: Key Points Of Flap Harvest Potential Advantagesmentioning
confidence: 99%
“…The keystone flap has been adopted in a number of centres internationally, but unlike other local flaps, there does not appear to be a clear biomechanical explanation for its apparent utility . A possible rationale for use of the keystone flap is the hypothesis that long‐axis relaxation of the island (EF in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In a case series of 3 patients, Gutman et al 4 safely and effectively demonstrated the use of keystone flaps for lumbosacral myelomeningocele closure. More recently, in a case series of 5 patients, Park et al 5 demonstrated the use of keystone flaps in lumbosacral myelomeningocele repair and concluded that it is an effective, reliable, and durable reconstructive option.…”
mentioning
confidence: 99%